An analysis on students’ difficulties in Intermediate English Grammar course - Paputungan, Fina Milenda; Helingo, Adimawati; Yulinda Rahmah, Illma (English Education Department, 2022)
The objective of this research is to analyze the students’ difficulties in learning intermediate grammar courses, especially in modal auxiliaries and reported speech materials as well as the factors of students’ difficulties in learning grammar in English Education Department at IAIN Sultan Amai Gorontalo. This research study used the qualitative method. The population was 10 students of third semester in English Education Department at IAIN Sultan Amai Gorontalo. Next, techniques of data collection were observation sheet and interview. The result showed that most students have not understood and confused to use all the modal auxiliaries, the use of “to” and without “to”, and they did not memorize the formulas pattern of positive, negative and interrogative sentence. Also, students were confused in displacement of tenses because they did not know the formula, and were confused how to use pronoun and time pronoun because they did not memorize. Furthermore, factors that affect the students’ difficulties in learning grammar start from a lack motivation, learning strategies, teaching methods, educational background and family environment.